Impact of the Early Start Denver Model on the cognitive level of children with autism spectrum disorder: study protocol for a randomised controlled trial using a two-stage Zelen design. Issue 3 (27th March 2017) - Touzet, Sandrine; Occelli, Pauline; Schröder, Carmen; Manificat, Sabine; Gicquel, Ludovic; Stanciu, Razvana; Schaer, Marie; Oreve, Marie-Joelle; Speranza, Mario; Denis, Angelique; Zelmar, Amelie; Falissard, Bruno; et al.
Abstract : Introduction: Early intervention for autism spectrum disorder (ASD) in the European French-speaking countries is heterogeneous and poorly evaluated to date. Early intervention units applying the Early Start Denver Model (ESDM) for toddlers and young children with ASD have been created in France and Belgium to improve this situation. It is essential to evaluate this intervention for the political decision-making process regarding ASD interventions in European French-speaking countries. We will evaluate the effectiveness of 12 hours per week ESDM intervention on the cognitive level of children with ASD, over a 2-year period. Methods and analysis: The study will be a multicentre, randomised controlled trial, using a two-stage Zelen design. Children aged 15–36 months, diagnosed with ASD and with a developmental quotient (DQ) of 30 or above on the Mullen Scale of Early Learning (MSEL) will be included. We will use a stratified minimisation randomisation at a ratio 1:2 in favour of the control group. The sample size required is 180 children (120 in the control and 60 in the intervention group). The experimental group will receive 12 hours per week ESDM by trained therapists 10 hours per week in the centre and 2 hours in the toddlers' natural environment (alternatively by the therapist and the parent). The control group will receive care available in the community. The primary outcome will be the change in cognitive level measured with the DQ of the MSEL scored at 2 years. Secondary outcomes will include change in autism symptoms, behavioural adaptation, communicative and productive language level, sensory profile and parents' quality of life. The primary analysis will use the intention-to-treat principle. An economic evaluation will be performed. Dissemination: Findings from the study will be disseminated through peer reviewed publications and meetings. Trial registration number: NCT02608333 (clinicaltrials.gov); Pre-results.